2016
DOI: 10.1042/bsr20160104
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics changes caused by the fusion of human embryonic stem cell and ovarian cancer cells

Abstract: To observe the effect of gene expression and tumorigenicity in hybrid cells of human embryonic stem cells (hESCs) and ovarian cancer cells in vitro and in vivo using a mouse model, and to determine its feasibility in reprogramming tumour cells growth and apoptosis, for a potential exploration of the role of hESCs and tumour cells fusion in the management of ovarian cancer. Stable transgenic hESCs (H1) and ovarian cancer cell line OVCAR-3 were established before fusion, and cell fusion system was established to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Considering that aggressive tumor cells have similar proliferation and plasticity properties to ESCs, PTEN regulation in the ESC microenvironment instead of the tumor microenvironment (TME) represents an ideal intervention to prevent early-stage tumorigenesis [ 10 ]. In addition, enhanced expressions of P53 and PTEN promote the expression levels of caspase 9 in human ESCs, but inhibit AKT phosphorylation and tumor growth, demonstrating that the PTEN-P53 signaling pathway governs cell cycle exit in tumors [ 11 ]. As a typical tumor suppressor gene, loss-of-function in PTEN can result in a deficiency of tumor suppressor signaling in the downstream cascades, providing a favorable environment for tumor growth.…”
Section: Pten and Pluripotent Stem Cellsmentioning
confidence: 99%
“…Considering that aggressive tumor cells have similar proliferation and plasticity properties to ESCs, PTEN regulation in the ESC microenvironment instead of the tumor microenvironment (TME) represents an ideal intervention to prevent early-stage tumorigenesis [ 10 ]. In addition, enhanced expressions of P53 and PTEN promote the expression levels of caspase 9 in human ESCs, but inhibit AKT phosphorylation and tumor growth, demonstrating that the PTEN-P53 signaling pathway governs cell cycle exit in tumors [ 11 ]. As a typical tumor suppressor gene, loss-of-function in PTEN can result in a deficiency of tumor suppressor signaling in the downstream cascades, providing a favorable environment for tumor growth.…”
Section: Pten and Pluripotent Stem Cellsmentioning
confidence: 99%
“…However, it is not always the case that fusion cells will exhibit increased tumorigenicity or TSC-like properties. He et al (51) reported in 2017 that hESCs and ovarian cancer cells can fuse in vitro spontaneously, and the fused cells interestingly exhibited epigenetic changes that led to inhibition of growth, which may provide a novel direction for the treatment of ovarian cancer. Although cell fusion between BMDCs and somatic cells may be the origin of TSCs, the hybrid cells that form as a result of the fusion of human HSCs and esophageal carcinoma cells did not generate esophageal TSCs (52,53).…”
Section: Cell-cell Fusion In Vitro In Cancermentioning
confidence: 99%